Peningkatan Kesiapan Adaptasi Kerja melalui Pelatihan Workplace Adaptability pada Staf Housekeeping Hotel (Lembaga Pengembangan Kinerja Dosen, 2026)
The hospitality industry is a dynamic sector that demands housekeeping staff to have high adaptability to changes in technology, operational procedures, and guest expectations. This study aims to evaluate the effectiveness of workplace adaptability training in increasing the understanding and adaptation readiness of housekeeping staff at PT X. The research method used was a quasi-experimental design with a one-group pre-test post-test model. Training participants included various job levels, from staff to supervisors. The intervention was carried out through the delivery of conceptual material, discussion of operational case studies, and online reflective sessions. The comparative test results showed a significant difference between the participants' level of understanding before and after the training. All participants experienced a consistent increase in scores, indicating that this training was effective in building employees' cognitive capacity and adaptive behavior. However, the effectiveness of this training needs to be supported by inclusive organizational policies, fair compensation systems, and protection against work risks to reduce the turnover rate of new and daily workers. The study concludes that adaptability training is a vital investment for hotel operational resilience amidst market dynamics.